A Constituição de 1824 e o problema da modernidade: o conceito moderno de Constituição, a história constitucional brasileira e a Teoria da constituição no Brasil - David Francisco Lopes Gomes (2016)
This thesis addresses three problems: the modern concept of Constitution; the reflections of this concept in the relationship between Brazilian constitutional theory and Brazilian constitutional historys interpretation; and the relationship between Brazil and Modernity. To deal with these problems, first the modern concept of Constitution is categorically reconstructed from the history of the Brazilian Constitution of 1824. This process of reconstruction unfolds in three moments: the narrative of the objective situation in which Brazil and Portugal were in the general context of the Old Regime crisis; the narrative of the changes, in that historical period, in the domains of public spaces and of the perception of the experienced temporality; and the narrative of the deep changes that have disrupted the traditional bases of law and politics. Second, the conceptual structure of Marcelo Neves thesis about the symbolic constitucionalization is critically explored, as an example of the internal and reciprocal conditioning of Brazilian constitutional theory and Brazilian contitutional historys interpretation. Third, a concept of Modernity is developed to ground a conclusion about the relationship between Brazil and Modernity and, retroactively, about the modern concept of Constitution. From a methodological point of view, the historical methodology is offered by economic history, conceptual history (Begriffsgeschichte) and the Cambridge contextualism. The main historical sources utilized are: the proceedings of the Constituent and Legislative General Assembly of the Empire of Brazil of 1823; the texts of Friar Joaquim do Amor Divino Caneca; and the manuscripts and printed pamphlets published from 1820 to 1823, apart from other official documents and secondary sources. Finally, the theoretical support is provided by a critical dialogue between Karl Marx and Jürgen Habermas.